GIS-basierte Analyse der Morphometrie und räumlichen Verteilung von Seen im Lena-Delta, NO-Sibirien. - Morgenstern, Anne; Röhr, Christina; Grosse, Guido; Grigoriev, Mikhail N (PANGAEA, 2011)
This data set provides a detailed inventory of lakes in the Lena Delta, northern Siberia, with respect to the lakes' association with one of the three geomorphological main terraces of the Lena Delta. The inventory is based on Landsat-7 ETM+ image data and spatial analysis in a Geographical Information System (GIS). Several morphometric lake attributes were determined from the resulting dataset and statistically analyzed. Significant differences in the morphometric lake characteristics allowed the distinction of a mean lake type for each main terrace. The lake types reflect the special lithological and cryolithological conditions and geomorphological processes prevailing on each terrace. In Morgenstern et al. (2008), special focus was laid on the investigation of lake orientation and the discussion of possible mechanisms for the evolution of the second terrace's oriented lakes.
The Lena River Delta - inventory of lakes and geomorphological terraces
Keywords: Comment; File size; LenaDelta_2nd_terrace; LenaDelta_3rd_terrace; LenaDelta_lakes; LenaDelta_lakes_divided; Lena Delta, Siberia, Russia; Remote Sensing of POlar Non-glaciated and Sensitive Environments; RESPONSE; Sampling on land; Uniform resource locator/link to file; Uniform resource locator/link to image